2(22-x)-3x=26

Simple and best practice solution for 2(22-x)-3x=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(22-x)-3x=26 equation:


Simplifying
2(22 + -1x) + -3x = 26
(22 * 2 + -1x * 2) + -3x = 26
(44 + -2x) + -3x = 26

Combine like terms: -2x + -3x = -5x
44 + -5x = 26

Solving
44 + -5x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-44' to each side of the equation.
44 + -44 + -5x = 26 + -44

Combine like terms: 44 + -44 = 0
0 + -5x = 26 + -44
-5x = 26 + -44

Combine like terms: 26 + -44 = -18
-5x = -18

Divide each side by '-5'.
x = 3.6

Simplifying
x = 3.6

See similar equations:

| 2a^3-16a^2+30a= | | 2(11+8n)=12n | | x^6-b^9= | | 7/8n-3=5/8n+12 | | y/1.75=11 | | x/3-8=-10 | | x^4+6x^3+9x^2+12x+4=0 | | 5(1x+4)=7x-26 | | 15+4p=23 | | x^4+6x^3+9x^3+12x+4=0 | | (q^-2)^4/(q^5a^-3)^-3 | | 2n-7=5 | | (2x+1)3x(x-4)=0 | | x^2-14-5x=0 | | 12p+7q=3r | | 4(x+5)=7x+18-3x+2 | | 4/7=-7/5v | | 34.6/1.081 | | y=(x+1)(6x-6)-6x^2 | | -5x+2=-1 | | 30.6/1.068 | | 22=34-b | | 7x-5=3+4x | | 28=b(b-3) | | 2/7+2/7=-4/5v-3/5v | | sx-5=9 | | 2(2x+4)=3x+12 | | 18x^2-132x+242=0 | | 8(x+1)-11=53 | | x+0.068x= | | x+x+5+2(x+5)=431 | | 3x+-14=x |

Equations solver categories